The significances of the final -h as a marker of entering tone characters in romanized Chines text in the Qing dynasty - Wong, Lingyan (2001)
The significance of the final -h as a marker in Romanized Chinese texts in the Qing Dynasty can be summed up into three points as below: 1. the final -h marker of the entering tone; 2. The final -h does not have any independent meaning, neither a marker of tone category; 3. The final -h indicates a short intonation. Based on the pronunciation of entering tone character which noted in Romanized Chinese Texts in the Qing Dynasty and the investigation and research of Modern Dialects, this article aims to discuss the significances of the final -h of entering tone characters which recorded by the Westerners to China inthe nineteenth century.